'Kids sold, desperate moms need cash': Media representations of Zimbabwean women migrants. Issue 2 (30th June 2016) - Mawadza, Aquilina; Banda, Felix
Abstract: The article draws on 575 randomly selected articles from the South African Media database to explore the representation of Zimbabwean women migrants. Using critical discourse analysis (CDA), the article shows that some of the dominant construction types depict a picture of caricatured, stereotypical and stigmatised Zimbabwean migrant women without voice and individuality. In turn, the diversity of their actualities is not captured in the process of constructing the twin images of Zimbabwean women as victims and as purveyors of decadent and other negative social ills in society. We conclude that Zimbabwean women migrants appear in the SA media primarily in three negative images: suppliers of sexual services, as un-motherly, and as victims. We also conclude that there is need for media to capture the voices of migrant women recounting their everyday lived experiences in different political and socio-economic contexts in order to account for the migrant women's voices of resilience, defiance and victimhood and of agency, against the normalising and marginalising influences of political institutions and national border controls. This would also help capture the transformative nature of migration to the women, the 'home' in Zimbabwe and the 'home' in South Africa.